Q: What is 13 plus 12 times negative 6 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-12

6

Well there are quite a few numbers that added together will equal negative 15: here are just a few examples: negative 1 plus negative 14 equals negative 15 (-1 + -14 = -15) negative 2 plus negative 13 equals negative 15 (-2 + -13 = -15) negative 3 plus negative 12 equals negative 15 (-3 + -12 = -15) negative 4 plus negative 11 equals negative 15 (-4 + -11 = -15) negative 5 plus negative 10 equals negative 15 (-5 + -10 = -15) negative 6 plus negative 9 equals negative 15 (-6 + -9 = -15) negative 7 plus negative 8 equals negative 15 (-7 + -8 = -15) negative 30 plus positive 15 equals negative 15 (-30 + 15 = -15) negative 29 plus positive 14 equals negative 15 (-29 + 14 = -15) negative 28 plus positive 13 equals negative 15 (-28 + 13 = -15) and on an on it goes.

12

4 x (-3) = (-12)-12 +9 = (-3)so the answer is -3

Related questions

3*-5+27 equals 12.

-12

6

-24

Seventy plus negative 12, or seventy minus 12 (same thing) is equal to 58.

12

Well there are quite a few numbers that added together will equal negative 15: here are just a few examples: negative 1 plus negative 14 equals negative 15 (-1 + -14 = -15) negative 2 plus negative 13 equals negative 15 (-2 + -13 = -15) negative 3 plus negative 12 equals negative 15 (-3 + -12 = -15) negative 4 plus negative 11 equals negative 15 (-4 + -11 = -15) negative 5 plus negative 10 equals negative 15 (-5 + -10 = -15) negative 6 plus negative 9 equals negative 15 (-6 + -9 = -15) negative 7 plus negative 8 equals negative 15 (-7 + -8 = -15) negative 30 plus positive 15 equals negative 15 (-30 + 15 = -15) negative 29 plus positive 14 equals negative 15 (-29 + 14 = -15) negative 28 plus positive 13 equals negative 15 (-28 + 13 = -15) and on an on it goes.

negative 1

Negative 9 + positive 3 = -6 and negative six - negative 3 is -9.Vanessa Hudgensage 12

3-(-9) Considering a negative plus a negative equals a positive your equation can be rewritten as 3+9 Which equals 12

k = -1

4 x (-3) = (-12)-12 +9 = (-3)so the answer is -3